Situation Report: Czechoslovakia, 7 January 1986 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. A Subdued Vasil Bilak Makes His Point Specter of 1968 Raised to Deter Departure from Orthodoxy Party Official on the Unity of the Bloc The Budapest Forum as Seen by Prague Mixed Morale in Armed Forces: Army Low, Air Force High Prague Exercises Firm Control over Religious Activists and Dissidents Czechoslovak Dissidents and Nicaragua New Five-Year Economic Plan Unveiled A Good Harvest in 1985, but Prague Is Still Not Satisfied Not All Is Rotten in the State of Czechoslovakia Yugoslav Paper Anticipates Major Changes in Czechoslovak Economy / by Slobodan Stankovic